Post-secular Messianism Against the Law: Judith Butler on Walter Benjamin and ‘Sacred Life’ - Ball, Karyn (Law and critique, 2016)
This essay focuses on Judith Butler’s configuration in Parting Ways: Jewishness and the Critique of Zionism ( 2012a ) of sacred life from the mystical motifs that traverse Walter Benjamin’s writings as the pivot of an anti-identitarian ethics committed to non-violent resistance. To gain critical leverage on Butler’s post-secular stance, my analysis turns to Talal Asad’s ‘Redeeming the “Human” Through Human Rights’ chapter from Formations of the Secular ( 2003 ), where he enunciates a disparity between a ‘pre-civil state of nature’ and the notion of ‘inalienable rights’ that informs the subject’s rights under secular law. In underscoring the secular state’s inability or refusal to ascribe sacredness to ‘real living persons’ over and against ‘“the human” conceptualized abstractly, or imagined in a state of nature’ as presumed by natural law, Asad indirectly articulates what is at stake in Butler’s explication in Parting Ways of Benjamin’s ‘Critique of Violence’. In this context, Butler unpacks Benjamin’s remarks about the sixth commandment’s non-coercive disposition and the inner struggle its provisional applicability prompts. A conception of ‘sacred life’ crystallizes through Butler’s emphasis on the open-endedness of this struggle, which encourages us to abandon a solipsistic investment in our own suffering in the process of acknowledging its eternally transient rhythm. I argue that Butler supplements this motif by drawing upon Hannah Arendt’s grounding of the political in cohabitation. My contention is that while ‘sacred life’ forms the backbone of Butler’s affirmation of civil disobedience, Arendt empowers Butler’s ethics to transcend Benjamin’s Jewish-messianic melancholy by radicalizing the passivity that refracts it.